1346. The Tetrazole VT-1598 Is Efficacious in a Murine Model of Invasive Aspergillosis with a PK/PD Expected of a Mold-Active CYP51 Inhibitor. (26th November 2018) - Garvey, Edward P; Sharp, Andrew; Warn, Peter; Yates, Christopher M; Schotzinger, Robert J
Abstract: Background: VT-1598 is a novel fungal CYP51 inhibitor with potent in vitro activity against yeast, mold, and endemic pathogenic fungi (Wiederhold, JAC, 2017). Its tetrazole-based rational drug design imparts much greater selectivity vs. human CYPs (Yates, BMCL, 2017), which could reduce human CYP-related side effects and DDIs. We report here VT-1598's in vivo activity in an invasive aspergillosis (IA) model. Methods: MIC was determined as outlined in CLSI M38-A2. Plasma PK was measured after 4 days of oral doses in neutropenic ICR mice without fungal inoculation. In vivo antifungal activity was determined in a tail-vein IA model in neutropenic mice inoculated with A. fumigatus (AF) ATCC 204305 ( N = 10 per dose). Two separate studies were conducted, with oral VT-1598 treatment starting either 48 hours prior (prophylaxis) or 5 hours postinoculation (delayed), with 4 days of postinoculation dosing, and kidney fungal burden measured 1 day post last dose by both CFU and qPCR. Drug control was 10 mg/kg AmBisome i.v. Results: The MIC for VT-1598 against AF 204305 was 0.25 μg/mL. The plasma PK of VT-1598 was linearly proportional between the 5 and 40 mg/kg once-daily doses, with AUCs of 155 and 1, 033 μg h/mL for the two doses, respectively. VT-1598 was similarly effective in reducing fungal burden when given in delayed treatment compared with prophylaxis, and both studies demonstrated a full dose–response (i.e., no to full reduction of fungal burden). When comparing fungal burdens of each dose group to the fungal burden at the start of treatment, the dose of VT-1598 to achieve fungal stasis ranged from 20.5 to 25.9 mg/kg and to achieve a 1-log10 fungal kill ranged from 30.9 to 50.5 mg/kg. Using the previously measured mouse plasma binding (>99.9%), the free AUC /MIC values for stasis and 1-log10 kill ranged from 2.1–2.7 and 3.2–5.2, respectively. These values are within the range of 1–11 that have been reported for posaconazole and isavuconazole (Lepak, AAC, 2013). Conclusion: VT-1598 had potent antifungal activity in a murine model of IA. The PK/PD relationship was the same as clinically used mold-active CYP51 agents, suggesting that it could have similar clinical efficacy. If correct, the tetrazole-based greater selectivity may significantly differentiate VT-1598 from current IA therapies. Disclosures: E. P. Garvey, Viamet Pharmaceuticals, Inc.: Employee, Salary. A. Sharp, Evotec (UK) Ltd.: Employee, Salary. P. Warn, Evotec (UK) Ltd.: Employee, Salary. C. M. Yates, Viamet Pharmaceuticals, Inc.: Employee, Salary. R. J. Schotzinger, Viamet Pharmaceuticals, Inc.: Board Member and Employee, Salary.